In vivo biocompatibility and biodegradability of dextrin-based hydrogels - Moreira, Susana Margarida Gomes (2010)
The in vivo biocompatibility of dextrin hydrogels obtained by polymerization of dextrin-hydroxyethylmethacrylate (dextrin-HEMA) and dextrin-vinyl acrylate (dextrin-VA) are reported in this work. The histological analysis of subcutaneous implants of these hydrogels, featuring inflammatory and reabsorption events, were carried out over a 16-week period in mice. The dextrin-HEMA hydrogel was quickly and completely degraded and reabsorbed, whereas the dextrin-VA degradation occurred slowly and a thin fibrous capsule surrounded the nondegradable hydrogel. The dextrin-HEMA was degraded after 16 weeks with only mild inflammation and a few detectable foamy macrophages around the implant. These events were followed by complete resorption and no sign of capsule formation or fibrosis associated to the implants. The results indicate that the dextrin hydrogels are biocompatible because no toxicity on the tissues surrounding the implants was found. It may be speculated that a controlled degradation rate of the hydrogels may be obtained by grafting dextrin to HEMA and VA in different proportions.